ANALISIS PENERIMAAN DAN PENGGUNAAN APLIKASI ZOOM DENGAN PENDEKATAN MODEL UTAUT 2 - Ningsih, Siti Cahya; Setiawan, Dedy; Arsa, Daniel (Jurnal Informatika, Sistem Informasi dan Kehutanan (FORSINTA), 2023)
In pandemic era, teaching and learning process are conducted online by virtual application, which Zoom is one its popular application. Zoom is video conference application or online meeting with Screen Sharing concept. Acceptance students is one of importannt things to find out the succesful implementation of applicaiton. This study will identify factors that affect acceptance and use of Zoom application. Model that used were UTAUT2 model. Population were undergraduate students in Jambi University. The sampling technique used were Nonprobability Sampling with Purposive Sampling method and the number of samples are 394 respondents. The data analysis technique used were PLS-SEM (Partial Last Squares–Structural Equation Modeling) via SmartPLS 3 software. Based on hypothesis testing results it can be concluded that Facilitating Conditions, Hedonic Motivation, and Habit gave a significant effect of behavioral intention, while Habit And Behaviorial Intention gave a significant effect of Use Behavior.